Pengaruh Kualitas Alat Produksi Terhadap Volume Produksi Industri Tenun Sarung Di Lamongan - Maulida, Indira Shofia; Tholibin, Kholilut (Jurnal Ilmiah Administrasi Bisnis dan Inovasi, 2021)
The Effect of Production Tool Quality on The Production Volume of The Glove Weaving Industry in Lamongan. This study aims to determine the effect of the quality of the ATBM (non-machine weaving tool) production volume on the production volume of the woven sarong industry in Parengan village, Maduran district. contributes to the regional income of Lamongan district which is a sample of all weaving companies in Parengan village, Maduran District. The analysis methods used are: simple regression, t test analysis, and F test analysis where the independent variable (X) is the quality of the ATBM production equipment, and the dependent variable (Y) is the volume of production. In this research data collection, making an assessment of the quality of ATBM using indicators, including: (Construction Framework, Production Capacity, Movement and Age). Of the four indicators, the total value of the quality of the production tools will be grouped according to the number of assessments. The conclusion of the analysis, resulting in a Simple Linear Regression Equation: Å¶ = 71, 21 + 1.59X, it means that the quality of ATBM production has a positive effect on the volume of sarong production. Calculation of the coefficient of determination r2 = 0.752 = 0.5625 or the value of the production volume of 56.25% is determined by the quality of the production equipment, the remaining 43.75% is determined by other factors. From the regression coefficient value of the variable quality of production equipment of 1.59, it means that if the value of the quality of the production equipment for ATBM increases by 1, the value of the production volume of sarong increases by 1.59 per each Quality value.